Ecthyma Gangrenosum in Children With Cancer: Diagnosis at a Glance: A Retrospective Study From the Infection Working Group of Italian Pediatric Hematology Oncology Association. Issue 3 (10th February 2022) - Muggeo, Paola; Zama, Daniele; Decembrino, Nunzia; Onofrillo, Daniela; Frenos, Stefano; Colombini, Antonella; Perruccio, Katia; Calore, Elisabetta; Giurici, Nagua; Ficara, Monica; La Spina, Milena; Mura, Rosamaria; et al.
Abstract : Background: To depict ecthyma gangrenosum (EG) clinical presentation and evolution in a large multicenter pediatric retrospective collection of children with malignancies or bone marrow failure syndromes, to facilitate early diagnosis. Methods: EG episodes diagnosed in the period 2009–2019 were identified by a retrospective review of clinical charts at centers belonging to the Italian Pediatric Hematology Oncology Association. Results: Thirty-eight cases of EG occurring in children (male/female 16/22; median age 5.2 years) with hematologic malignancy (29), allogeneic stem cell transplantation (2) or relapsed/refractory solid tumor (3) were collected. The involved sites were: perineal region (19), limbs (10), trunk (6), head and the iliac crest (3). Bacteremia was present in 22 patients. Overall, the germs isolated were Pseudomonas aeruginosa (30), Stenotrophomonas maltophilia (3) and Escherichia coli (1); 31% of them were multidrug-resistant. All patients received antibacterial treatment, while surgery was performed in 24 patients (63.1%). Predisposing underlying conditions for EG were severe neutropenia (97.3%), corticosteroid treatment (71%) and iatrogenic diabetes (23.7%). All patients recovered, but EG recurred in 5 patients. Nine patients (24%) showed sequelae (deep scars, with muscle atrophy in 2). Four patients (10.5%) died, 1 due to relapse of EG with Carbapenem-resistant Enterobacteriaceae co-infection and 3 due to the progression of the underlying disease. Conclusions: EG requires early recognition and a proper and timely treatment to obtain the recovery and to avoid larger necrotic lesions, eventually evolving in scarring sequelae.